Urgensi Sertifikasi JULEHA terhadap Tempat Pemotongan Unggas Bebek Beton - Khoiriyah, Khoiriyah; Karim, Moh. (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
The large Muslim population in Indonesia has led to an increasing demand for halal meat. To ensure that the meat is slaughtered in accordance with Islamic law, JULEHA certification is essential. The importance of JULEHA certification lies in its ability to provide consumers with a guarantee that the meat they consume has been processed according to halal standards. This certification in poultry slaughtering aims to ensure that the slaughtering process complies with Islamic law, supports business sustainability, and guarantees that the raw materials used for halal meat processing are met. With the presence of JULEHA certification, the quality of products can be improved, halal integrity maintained, and consumer trust in poultry slaughtering facilities can be enhanced. This research is expected to contribute to the understanding of the importance of JULEHA certification in the culinary industry and among poultry slaughtering entrepreneurs. The method employed in this study is field research, utilizing a qualitative approach aimed at deeply understanding the significance of JULEHA in TPU Bebek Beton. The data sources used in this research include both primary and secondary data. Data collection techniques involved interviews, observations, and documentation. The results of this study indicate that JULEHA at TPU Bebek Beton possesses competency certification and has fulfilled the 13 competencies outlined in the SKNI. JULEHA has participated in training and education programs organized by Universitas Airlangga Surabaya.